Association of Premature Immune Aging and Cytomegalovirus After Solid Organ Transplant - Higdon, Lauren E.; Gustafson, Claire E.; Ji, Xuhuai; Sahoo, Malaya K.; Pinsky, Benjamin A.; Margulies, Kenneth B.; Maecker, Holden T.; Goronzy, Jorg; Maltzman, Jonathan S. (Frontiers in Immunology, 2021)
Immune function is altered with increasing age. Infection with cytomegalovirus (CMV) accelerates age-related immunological changes resulting in expanded oligoclonal memory CD8 T cell populations with impaired proliferation, signaling, and cytokine production. As a consequence, elderly CMV seropositive (CMV+) individuals have increased mortality and impaired responses to other infections in comparison to seronegative (CMV–) individuals of the same age. CMV is also a significant complication after organ transplantation, and recent studies have shown that CMV-associated expansion of memory T cells is accelerated after transplantation. Thus, we investigated whether immune aging is accelerated post-transplant, using a combination of telomere length, flow cytometry phenotyping, and single cell RNA sequencing. Telomere length decreased slightly in the first year after transplantation in a subset of both CMV+ and CMV– recipients with a strong concordance between CD57+ cells and short telomeres. Phenotypically aged cells increased post-transplant specifically in CMV+ recipients, and clonally expanded T cells were enriched for terminally differentiated cells post-transplant. Overall, these findings demonstrate a pattern of accelerated aging of the CD8 T cell compartment in CMV+ transplant recipients.